Hypothermia Management in Newborns Artificial Intelligence Based: Systematic Review - Rahmawati, Ika; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih; Walin, Walin (Journal of Maternal and Child Health, 2024)
Background: Hypothermia in newborns that is not treated properly will lead to respiratory failure and death. Hypothermia in newborns is 4 times more dangerous than hypothermia in adults. Care in the delivery room plays an important role in it. Neonatal service technology in the delivery room must be responsive, able to monitor and effective. Artificial intelligence can help determine management as needed. This study aims to analyze and examine the management of hypothermia in newborns based on artificial intelligence using the systematic review method. Subjects and Method: This study is a systematic review with PICO including: (1) Population: newborns; (2) Intervention: artificial intelligence; (3) conventional hypothermic treatment; (4) Artificial intelligence is feasible to be used in the management of neonatal hygiene.  The databases used are Google Scholar, PubMed, Science Direct, and Proquest. The inclusion criteria include fulltext in Indonesian and English with the study subject  of newborns with hypothermia. The exclusion criteria for this study are articles published under the last five years. Results: A total of 9 articles show that the existence of artificial intelligence can provide feedback support in the prevention of hypothermia efficiently and facilitate effective treatment. Conclusion: Hypothermic prevention feedback with artificial intelligence Fuzzy logic can save time and facilitate appropriate treatment.